2021
DOI: 10.1038/s41598-021-95812-y
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal structural evaluation in celiac disease

Abstract: This observational case–control study assessed the differences in choroidal structure between patients with celiac disease and healthy subjects utilizing the choroidal vascularity index (CVI). Seventy-four celiac patients and 67 healthy subjects underwent a complete ophthalmological evaluation, axial length (AL) measurements and spectral-domain optical coherence tomography with enhanced depth imaging mode (EDI SD-OCT) evaluation. These images were binarized and choroidal vasculature was analyzed. Choroidal tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Since then, CVI has been largely used for such a purpose in the international literature. 3 This technique in our opinion has a limitation because it can be influenced by the so-called blooming effect.…”
Section: Dear Editormentioning
confidence: 99%
“…Since then, CVI has been largely used for such a purpose in the international literature. 3 This technique in our opinion has a limitation because it can be influenced by the so-called blooming effect.…”
Section: Dear Editormentioning
confidence: 99%
“…In fact, the choroid of celiac patients appears thicker than healthy controls [ 8 , 9 ]. In particular, De Bernardo et al [ 9 ] not only confirmed a thicker choroid in celiac patients [ 8 ], but analyzing the choroidal vascularity index in these patients, found no statistical differences between celiac patients and healthy controls. However, celiac patients showed all the choroidal areas to be larger in a significant way than the healthy group.…”
Section: Introductionmentioning
confidence: 99%
“…However, celiac patients showed all the choroidal areas to be larger in a significant way than the healthy group. Thus, De Bernardo et al supposed a proportional increase in both the vascular and stromal components, that may be linked to the inflammatory and autoimmune responses related to celiac disease pathophysiology [ 9 ]. On the other hand, anterior eye segment changes due to celiac disease are still unclear [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have been published dealing with the use of these diagnostic tools to evaluate retinal and choroidal aspect in patients with systemic diseases, such as celiac disease ( 2 , 3 ), and some neurological disorders, such as multisystemic atrophy ( 4 ) and progressive supranuclear palsy ( 5 ).…”
mentioning
confidence: 99%